2018
DOI: 10.1590/0104-6632.20180354s20160664
|View full text |Cite
|
Sign up to set email alerts
|

MONITORING OF BIOSURFACTANT PRODUCTION BY Bacillus subtilis USING BEET PEEL AS CULTURE MEDIUM VIA THE DEVELOPMENT OF A NEURAL SOFT-SENSOR IN AN ELECTRONIC SPREADSHEET

Abstract: This work investigated the combination of agitation and aeration conditions in a bench-bioreactor to identify the optimal biosurfactant production from substrate based on beet peel and glycerol from a biodiesel process. Thus, a central composite rotatable design (CCRD) and responses were evaluated by response surface methodology (RSM) modeling. The optimal operation values determined were 200 rpm (agitation) and 0.5 vvm (aeration), reaching values of 1931.2 mg/L of crude biosurfactant concentration and 28.37 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
(19 reference statements)
1
2
0
Order By: Relevance
“…This suggests that Bacillus subtilis may have utilized surfactin as a carbon source to help its maintenance and survival in the fermentation. The same behavior was reported by Santos et al (2018). In order to avoid the biosurfactant consumption, Shaligram and Singhal (2010) suggested that batch fermentation for surfactin production should be ended at an appropriate time.…”
Section: Time-course Profile Of Surfactin Productionsupporting
confidence: 63%
“…This suggests that Bacillus subtilis may have utilized surfactin as a carbon source to help its maintenance and survival in the fermentation. The same behavior was reported by Santos et al (2018). In order to avoid the biosurfactant consumption, Shaligram and Singhal (2010) suggested that batch fermentation for surfactin production should be ended at an appropriate time.…”
Section: Time-course Profile Of Surfactin Productionsupporting
confidence: 63%
“…Different renewable feedstocks as substrates in fermentation bioprocesses have been studied. These include rice straw (Panjiar et al, 2020), sugarcane bagasse (Marcelino et al, 2019) corncobs (Sari et al, 2020), corn husk (Saimmai et al, 2018), banana stalks (Asgher et al, 2020), pineapple peels (Vieira et al, 2021), orange peels (Sari et al, 2020), beetroot peels (Dos Santos et al, 2018) and others. Using Achromobacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the rapid development of artificial intelligence (AI) technology has made the intelligentization of microbial fermentation processes a hot topic (Coşgun et al, 2021; Gao et al, 2021; Santos et al, 2017; Wang et al, 2023). Due to their multidimensionality and complex implicit relationships, microbial fermentation data can be processed using AI technology based on artificial neural networks (ANN).…”
Section: Introductionmentioning
confidence: 99%